Cervical Cancer: A Global Health Crisis. Issue 11 (November 2017) - Small, William; Bacon, Monica A.; Bajaj, Amishi; Chuang, Linus T.; Fisher, Brandon J.; Harkenrider, Matthew M.; Jhingran, Anuja; Kitchener, Henry C.; Mileshkin, Linda R.; Viswanathan, Akila N.; Gaffney, David K.
Abstract : (Abstracted from Cancer 2017;123:2404–2412) One of the common malignancies in women and causes of cancer death worldwide is cervical cancer. Infection with the human papillomavirus is responsible for nearly all cases of cervical cancer.